The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1001/archderm.143.4.488
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Outcomes for Medicare Patients

Abstract: To determine whether a difference in melanoma outcomes exists in the United States between tumors detected by dermatologists vs those detected by nondermatologists.Design: Retrospective analysis of linked data from the Medicare enrollment and claims files from the Centers for Medicare and Medicaid Services and the National Cancer Institute's Surveillance, Epidemiology, and End Results program database from 1991 to 1996. The registries are from 12 US sites.Patients: A study sample comprised of 2020 subjects.Mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(19 citation statements)
references
References 37 publications
0
18
1
Order By: Relevance
“…41 Our study did not find any difference in stage at diagnosis for subjects having ambulatory visits to only dermatologists compared with those having visits only to PCPs. The best outcomes, however, were seen among patients who had previous ambulatory visits to both dermatologists and PCPs, suggesting that these services can complement one another.…”
Section: Discussioncontrasting
confidence: 73%
“…41 Our study did not find any difference in stage at diagnosis for subjects having ambulatory visits to only dermatologists compared with those having visits only to PCPs. The best outcomes, however, were seen among patients who had previous ambulatory visits to both dermatologists and PCPs, suggesting that these services can complement one another.…”
Section: Discussioncontrasting
confidence: 73%
“…Overall survival was worse among the group >50 and age was a significant prognostic variable in multivariate analysis13. Data from the SEER database and Medicare enrollment and claims files, showed that increasing age after 65 years and melanoma detection by a dermatologist were significantly predictive of survival on multivariate analysis in a population of over 2000 patients 14. In a large dataset of 17,600 melanoma patients, age was an independent prognostic factor for overall survival which was consistent within each thickness subgroup9.…”
Section: Discussionmentioning
confidence: 87%
“…In addition to the stage of melanoma at diagnosis, previous surveys (3)(4)(5)(6) have found that other prognostic factors such as age, sex, histology, and location are related to melanoma survival. In this investigation, we analyzed the data from the Cancer Registry to research melanoma-specific one-year, five-year, and ten-year survival dependent on the demographic and clinical factors.…”
Section: Introductionmentioning
confidence: 99%